Problems of assessing the financial security of a region - I. A. Elovsky; S. V. Zenchenko (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Assessing the financial security of a region is an important task for ensuring sustainable economic growth and social well-being of a constituent entity of the Federation. This article discusses the key issues associated with assessing financial security at the regional level. The main aspects include identification and analysis of factors influencing financial stability, such as income level, state of budget policy, debt burden and investment attractiveness. The complexity of developing a unified assessment methodology that takes into account the specifics and characteristics of each region is also considered. Much attention is paid to the relationship between financial security and other aspects, such as social development, infrastructure and ecology. Particular attention is paid to the need to introduce modern tools and approaches to monitoring and assessing financial security, which will allow timely identification of threats and development of effective strategies to overcome them. The study emphasizes the importance of an integrated approach to assessing financial security as a key condition for improving the standard of living of the population and achieving sustainable development at the regional level.Goal. Research and analysis of problems of assessing the financial security of a region, identification of key factors influencing its level, as well as development of recommendations for improving existing methodological approaches.Materials and methods. The study is based on the analysis of statistical data on the budget, long-term liabilities and macroeconomic indicators; correlation and regression analysis, clustering and economic and mathematical modeling were used to identify cause-and-effect relationships between financial security and various economic parameters of the region.Results and discussion. In the course of the work, the author's system of coefficients was developed that comprehensively assess the financial security of the region, as well as criteria for qualifying regions by the level of financial security.Conclusion. Based on the results of the study, it can be concluded that the assessment of the financial security of the regions is a multifactorial process that takes into account both quantitative and qualitative indicators that underlie the budget strategy of the region.